2012
DOI: 10.1002/hlca.201100375
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Range of the Titanium TADDOLate Catalyzed Asymmetric Fluorination of Activated Carbonyl Compounds

Abstract: The substrate range of the [TiCl2(TADDOLate)] (TADDOL=α,α,α′,α′‐tetraaryl‐1,3‐dioxolane‐4,5‐dimethanol)‐catalyzed asymmetric α‐fluorination of activated β‐carbonyl compounds has been investigated. Optimal conditions for catalysis are characterized by using 5 mol‐% of TiCl2(naphthalen‐1‐yl)‐TADDOLate) as catalyst in a saturated (0.14 mol/l) MeCN solution of F‐TEDA (1‐(chloromethyl)‐4‐fluoro‐1,4‐diazoniabicyclo[2.2.2]octane bis‐[tetrafluoroborate]) at room temperature. A series of α‐methylated β‐keto esters (3‐o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 65 publications
1
28
0
Order By: Relevance
“…Here, we prepared the 2-methylated b-ketoesters observing no issues regarding dialkylation. Our protocol avoids the use of strong bases and acylating reagents and leads to both, yields and scope, comparable or even better than those reported in literature [27,29,32,33,[55][56][57][58][59][60]. This was clearly shown for compound 3b, where different methodologies and their respective yields are presented (Scheme 6) [27,29,33,[55][56][57].…”
Section: Resultssupporting
confidence: 66%
“…Here, we prepared the 2-methylated b-ketoesters observing no issues regarding dialkylation. Our protocol avoids the use of strong bases and acylating reagents and leads to both, yields and scope, comparable or even better than those reported in literature [27,29,32,33,[55][56][57][58][59][60]. This was clearly shown for compound 3b, where different methodologies and their respective yields are presented (Scheme 6) [27,29,33,[55][56][57].…”
Section: Resultssupporting
confidence: 66%
“…When milder NFSI or NFPY-BF 4 was used as the fluorinating reagent instead of highly reactive Selectfluor, increased enantioselectivity was observed for such highly enolized substrates but not for nonenolized substrates, but the reactions using these reagents were very slow. 197199…”
Section: Modern Methods For Construction Of Quaternary C–f Stereogenimentioning
confidence: 99%
“…From this report until 2010 a range of metal catalysed fluorination reactions have been developed and previously reviewed [43]. Some years later, in 2012, Togni's group in a remarkable paper mainly dedicated to acyclic 1,3-dicarbonyl compounds, reported that using the same Ti/TADDOL complex the cyclic tetralone 16 (Scheme 1), gave the α-fluorinated product in 20% ee (entry 20, Table 1) [44]. We will comment on these results on acyclic 1,3-dicarbonyl later on.…”
Section: Metal-catalyzed Methodsmentioning
confidence: 99%
“…Regarding the enantioinduction they are not so rigid and have more degrees of conformational freedom in comparison with cyclic 3-oxo esters. In 2012, Togni's group reported [44] that using the Ti/TADDOL complexes (1, Figure 2) and Selectfluor ® ( Figure 1) a series of alkyl α-methyl 3-oxobutanoates were fluorinated giving excellent yields (44-96%) and moderate ee (10 examples, 45-81% ee). In addition, alkyl α-methyl 3-oxopentanoates could be fluorinated with moderate to high selectivities (7 examples, 30-90% ee).…”
Section: Metal-catalyzed Methodsmentioning
confidence: 99%
See 1 more Smart Citation